2019
DOI: 10.3390/rel10090508
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Validation of Centrality of Religiosity Scale (CRS-10BR and CRS-5BR)

Abstract: The centrality of religiosity scale (CRS), available in three versions (with 5, 10 and 15 items), is a measuring instrument that identifies the central importance of religiosity in the psychological construction and in the behavior of an individual. According to the literature, five components together express the centrality of religion in life: Public practice, private practice, ideological, intellectual, and religious experience. These components are the ground on which religious constructs are formed and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
4
20
0
5
Order By: Relevance
“…It was introduced in 2003 and has been constantly and straightforwardly reproduced since then. Recently, two studies using translated versions of CRS-5 and CRS-10 in Brazil by Esperandio and colleagues (Esperandio et al 2019) and in Romania with CRS-15 by Huza (2019) confirmed this simple pattern yet again. of the basic model for the CRS.…”
Section: Interrelationship Of the Dimensions Of Religiositymentioning
confidence: 84%
See 1 more Smart Citation
“…It was introduced in 2003 and has been constantly and straightforwardly reproduced since then. Recently, two studies using translated versions of CRS-5 and CRS-10 in Brazil by Esperandio and colleagues (Esperandio et al 2019) and in Romania with CRS-15 by Huza (2019) confirmed this simple pattern yet again. of the basic model for the CRS.…”
Section: Interrelationship Of the Dimensions Of Religiositymentioning
confidence: 84%
“…Thus, religiosity becomes an attainable and extensive construct, which is easy to integrate into any kind of research on health-related, economic, political, educational and social topics to name a few examples. That is the reason why interest in application, translations and cultural adaptations of the CRS has remained unbroken in the last decade (e.g., Esperandio et al 2019;Fradelos et al 2018;Huza 2019;Zarzycka 2007). The showcase of the Religion Monitor demonstrates, on the one hand, the functionality of the CRS, and on the other hand it reveals its limitations.…”
Section: Introductionmentioning
confidence: 99%
“…It measures five core dimensions of religiosity: public practice, private practice, ideological, intellectual and religious experience. Validation studies have shown adequate overall psychometric qualities [59]. In this study, the 7-item version is used.…”
Section: Data Collectionmentioning
confidence: 99%
“…The CRS is widely used in various studies related to religiosity (e.g., some recent publications, Zarzycka et al 2020;Riegel 2020;Ackert et al 2020aAckert et al , 2020bEsperandio et al 2019;Huza 2018;Fradelos et al 2018). The Centrality of Religiosity Scale has a comprehensive and economic way of assessing personal religiosity by including the dimensions associated with ideology, intellect, religious experience, private, and public religious practices.…”
Section: Instruments and Analysesmentioning
confidence: 99%